Outcomes of corneal neurotisation using processed nerve allografts: a multicentre case series. Issue 3 (16th November 2020) - Sweeney, Adam R; Wang, Margaret; Weller, Christopher L; Burkat, Cat; Kossler, Andrea L.; Lee, Bradford W; Yen, Michael T
Abstract : Background: Corneal neurotisation is a rapidly evolving procedure treating neurotrophic keratopathy. The variety of surgical techniques used and corresponding outcomes after corneal neurotisation are not well understood. This study describes the techniques and outcomes in the largest case series of corneal neurotisation using processed nerve allografts to date. Methods: This is a retrospective case series of patients who underwent corneal neurotisation with human cadaveric processed nerve allografts. All patients had preoperative and postoperative description of best corrected visual acuity and measurement of corneal sensation. Comparative studies after stratification of techniques were performed. Results: A total of 17 patients were identified. The cause of corneal anaesthesia was prior infection in eight cases, trigeminal nerve palsy in eight cases and ocular trauma in one case. There were no intraoperative or postoperative complications. Following neurotisation surgery, the time to first gain of corneal sensation and maximal gain of sensation occurred at a mean of 3.7 months (range 1–8 months) and 6.6 months (range 3–15 months), respectively. The mean preoperative and postoperative corneal sensation as measured by Cochet-Bonnet aesthesiometry was 0.36 cm (range 0–3.2 cm) and 4.42 cm (range 0–6 cm), respectively (p<0.01). Visual acuity was unchanged after neurotisation. There were no statistical differences in outcomes based on end-to-end versus end-to-side coaptations, donor nerve selection or laterality of donor nerve. Conclusion: Corneal neurotisation with processed nerve allografts is a safe and effective procedure. This study provides further evidence for the use of processed nerve allografts for corneal neurotisation.